Mapping Microbial Response Metabolomes for Induced Natural Product Discovery - Derewacz, Dagmara K; Covington, Brett C; McLean, John A; Bachmann, Brian O (ACS chemical biology, 2015)
Intergeneric microbial interactions may originate a significant fraction of secondary metabolic gene regulation in nature. Herein, we expose a genomically characterized Nocardiopsis strain, with untapped polyketide biosynthetic potential, to intergeneric interactions via coculture with low inoculum exposure to Escherichia, Bacillus, Tsukamurella, and Rhodococcus. The challenge-induced responses of extracted metabolites were characterized via multivariate statistical and self-organizing map (SOM) analyses, revealing the magnitude and selectivity engendered by the limiting case of low inoculum exposure. The collected inventory of cocultures revealed substantial metabolomic expansion in comparison to monocultures with nearly 14% of metabolomic features in cocultures undetectable in monoculture conditions and many features unique to coculture genera. One set of SOM-identified responding features was isolated, structurally characterized by multidimensional NMR, and revealed to comprise previously unreported polyketides containing an unusual pyrrolidinol substructure and moderate and selective cytotoxicity. Designated ciromicin A and B, they are detected across mixed cultures with intergeneric preferences under coculture conditions. The structural novelty of ciromicin A is highlighted by its ability to undergo a diastereoselective photochemical 12-π electron rearrangement to ciromicin B at visible wavelengths. This study shows how organizing trends in metabolomic responses under coculture conditions can be harnessed to characterize multipartite cultures and identify previously silent secondary metabolism.